Powerpoint applications in EFL teaching and learning at Can Tho high schools : - Đinh, Kim Oanh (Can Tho University, 2009)
This study examined how teachers implement PPT software in language teaching through investigation of teachers' EFL lessons, task types, reasons for using PPT and lesson designs.